2017
DOI: 10.7454/mst.v21i2.3080
|View full text |Cite
|
Sign up to set email alerts
|

Residual Stress Measurements on the TIG Weld Joint of 57Fe15Cr25Ni Austenitic Steel for Structural Material Applications by Means X-Ray Diffraction Techniques

Abstract: Measurements of residual stress on the 57Fe25Cr15Ni steel plate with no-filler TIG-welding process were carried out. This work was conducted to determine the nature of weld ability in synthesized steel. The bulks were formed in a dimension of 30x20x7 mm 3 to ease data retrieval. Results show that the largest residual stress occurred in the weld metal area, amounting to 82.40 MPa with lattice stretching of 0.18%. Conversely, the values decreased to 65.92 MPa and a stretch of 0.14% in the HAZ area. This residual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…This was identified to be the same phase as large precipitates. The mechanisms of hardening and corrosion (as well as oxidation resistance) in high alloyed steel are well known, and they have been reported in many publications (Sumijanto et al, 2015;Parikin et al, 2017;Besnard et al, 2017;Geers et al, 2017). In this work, it was assumed that the hardening mechanism of the alloy was associated with the presence of precipitation.…”
Section: Crystal Structurementioning
confidence: 98%
“…This was identified to be the same phase as large precipitates. The mechanisms of hardening and corrosion (as well as oxidation resistance) in high alloyed steel are well known, and they have been reported in many publications (Sumijanto et al, 2015;Parikin et al, 2017;Besnard et al, 2017;Geers et al, 2017). In this work, it was assumed that the hardening mechanism of the alloy was associated with the presence of precipitation.…”
Section: Crystal Structurementioning
confidence: 98%
“…In Figure 3A, according to the EDX measurements from previous studies [8], the light area contains abundant nickel, otherwise the dark area is poor. Carbon diffuses along the grain boundaries (see blue rectangle in Figure 3A) and looks like a black streak.…”
Section: Figure 3 Microstructures Of Specimen Around the Tig Weld Jomentioning
confidence: 77%
“…Other studies [8], [13], [18] reported that chromium carbide (Cr23C6) precipitation could also affect the increase in material hardness.…”
Section: Figure 5 Crystal Structures Of the Specimen Subjected To Timentioning
confidence: 99%
See 2 more Smart Citations